Shupihui: Revista - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1983)
Shupihui: Revista Latinoamericana de Actualidad y Análisis apareció en 1976 como un boletín de la Coordinación Pastoral de la Selva (Perú), dirigido a los agentes pastorales con temas sobre actualidad religiosa latinoamericana. La revista se comprometió a ser una voz orientadora, esclarecedora y divulgadora en la amazonia peruana para los diversos temas existentes de actualidad y analisis de latinoamerica y el mundo. En enero - marzo de 1983, surgió la publicación de la revista Shupihui volumen 08, numero 25-26, bajo la dirección del Padre Joaquin Garcia, en este número de shupihui tiene como objetivo brindar una pequeña contribución a la reflexión de fe de aquellos que no estamos trabajando en esos campos, es decir brindar ayuda a las comunidades, es evidente que en la situación actual de Centroamérica, el cristianismo en su conjunto tiene una gran responsabilidad de demostrar su pureza y abrir la puerta a los millones de hombres oprimidos que viven en el continente.

Shupihui: Latin American magazine of Actuality and Analysis appeared in 1976 as a bulletin of the Pastoral Coordination of the Jungle (Peru), directed to the pastoral agents with topics on Latin American religious actuality. The magazine was committed to be a guiding, enlightening and disseminating voice in the Peruvian Amazon for the various existing issues of current affairs and analysis of Latin America and the world. In April - June 1979, the publication of the magazine Shupihui volume 04, number 10, under the direction of Father Joaquin Garcia, John Paul II has given direct and personal attention to the indigenous world of each town he visited. In his speeches we find a doctrine that has clearly changed, there is also a pastoral tone, which is the result of certain findings that he has surely made, observing directly the indigenous people, their difficulties and the immense richness of their culture. In 1985, the pope will visit Iquitos for the first time to meet with the indigenous peoples, which will leave a historical mark in the country, and reflects the work of the Peruvian bishops in providing a timely service to discover and relieve Jesus Christ, from the heart of the indigenous peoples of our continent.
Shupihui: Magazine
Keywords: Iquitos (Peru)--periodicals Peru--general periodicals Peru--periodicals Iquitos (Perú)--revistas Perú--revistas generales Perú--revistas